FAKTOR LINGKUNGAN KONSUMEN, KELOMPOK ACUAN DAN E-WOM DALAM EKOSISTEM MEDIA SOSIAL : STUDI KASUS VIRAL MARKETING ALDIS BURGER - Fajrina Fatil Minati; Yuliani Setia Ningrum; silvy dewi anggraini; Aldi Saifulloh; irvaia miftakhul jannah; m. naizil ma'wqa; destania shezylia rossi putri (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
The development of social media has encouraged the emergence of various digital marketing strategies, one of which is viral marketing. The phenomenon of Aldis Burger promoted by Aldi Taher is interesting to study because of its success in attracting public attention through social media and the personal branding of public figures. This study aims to analyze consumer behavior in responding to Aldis Burger's viral marketing strategy based on cultural, demographic, economic, social, family and reference group factors, as well as technology and electronic word of mouth (e-WOM). The study uses a qualitative descriptive approach with the ADD case study method. The data source was obtained from an Instagram post @Bisnishack Official entitled